Usefulness of simultaneous screening for HIV‐specific and HCV‐specific antibodies and HBsAg by a capillary‐based multiplex rapid diagnostic test to strengthen linkage‐to‐care in sub‐Saharan patients attending sexually transmitted infection clinic. Issue 9 (25th May 2018) - Longo, Jean De Dieu; Mboumba Bouassa, Ralph‐Sydney; Mbeko Simaleko, Marcel; Kouabosso, André; Mossoro‐Kpinde, Christian Diamant; Robin, Leman; Charmant, Laura; Grésenguet, Gérard; Bélec, Laurent
Abstract : Adult outpatients attending the main sexually transmitted infection clinic of Bangui, Central African Republic, were prospectively subjected to a multiplex rapid diagnostic test for human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV). In group I (n = 208) of patients already followed for HIV, 6 (2.9%) were unexpectedly negative, thus corresponding to false positive for HIV by the national HIV algorithm; hepatitis B surface antigen and HCV positivities were high (18.7% and 4.3%, respectively). In group II (n = 71) of patients with unknown HIV status, at least 1 chronic viral disease was diagnosed in 26 (36.6%) patients, including 5 (7.1%) HIV, 17 (23.9%) HBV, and 3 (4.2%) HCV infections.